Laboratory Animals in Research and Teaching : Ethics, Care, and Methods - Akins, Chana K.; Panicker, Sangeeta; Cunningham, Christopher L. (Washington, D.C. ; London : American Psychological Association, 2005)
Contains valuable information that college and high school instructors will need to establish and maintain laboratories at their institutions. The volume offers practical advice about administrative matters, ethical issues, and the guidelines and regulations for the care and feeding of animals.
An ethical foundation -- Dealing with the animal research controversy / Harold A. Herzog -- The ethics cascade / Nancy K. Dess & Richard W. Foltin -- Practical advice -- Conducting behavioral research : methodological and laboratory animal welfare issues / Nancy A. Ator -- Conducting behavioral research with animals at smaller institutions : veterinary care and facilities / Christine M. Parks -- Lessons from the field -- Conducting behavioral research with animals at smaller institutions : a case history / Jesse E. Purdy -- Using laboratory animals in teaching and research with limited resources / Donald F. Kendrick -- Using laboratory animals for undergraduate teaching in behavioral science / David A. Eckerman -- Using laboratory animals in high school facilities / Craig W. Gruber -- Overview of regulations -- Laws, regulations, and guidelines / Nelson Garnett -- Local institutional policies / John D. Strandberg.
Includes bibliographical references (p. 252-256) and index.
Keywords: Laboratory animals; Laboratory animals -- Behavior; Animal welfare; Animal experimentation